Candida albicans Multilocus Sequence Typing Clade I Contributes to the Clinical Phenotype of Vulvovaginal Candidiasis Patients - Zhu, Yuxia; Fang, Chao; Shi, Yu; Shan, Yingying; Liu, Xiaoping; Liang, Yiheng; Huang, Liting; Liu, Xinyang; Liu, Chunfeng; Zhao, Yin; Fan, Shangrong; Zhang, Xiaowei (Frontiers in Medicine, 2022)
Candida albicans is the most frequent fungal species responsible for vulvovaginal candidiasis (VVC), which exhibits distinct genetic diversity that is linked with the clinical phenotype. This study was aiming at assessing the genotypes and clinical characteristics of different C. albicans isolates from VVC patients. Based on multilocus sequence typing (MLST), clade 1 was identified as the largest C. albicans group, which appeared most frequently in recurrent VVC and treatment failure cases. Further study on antifungal susceptibility demonstrated that MLST clade 1 strains presented significantly higher drug resistance ability than non-clade 1 strains, which result from the overexpression of MDR1. Moreover, the mRNA and protein expression levels of viru-lence-related genes were also significantly higher in clade 1 than in non-clade 1 isolates. Proteo-mic analysis indicated that the protein stabilization pathway was significantly enriched in clade 1 strains and that RPS4 was a central regulator of proteins involved in stress resistance, adher-ence and DNA repair, which all contribute to the resistance and virulence of MLST clade 1 strains. This study was the first attempt to compare the correlation mechanism between C. albi-cans MLST clade 1 or non-clade 1 strains and clinical phenotype, which is of great significance for VVC classification and treatment.